Investment Policy Review - Botswana - Conference des Nations Unies sur le commerce et le développement (United Nations, 2003)
Foreign Direct Investment (FDI) has been the driving force in moving the economy of Botswana from that of a least developed country status to one of a middle-income country. The country aims to continue this rapid growth while at the same time diversifying its economy. This paper reveals how the government plans to develop national business development through citizen empowerment, while at the same continuing to seize opportunities to attract FDI. The following topics are covered in this report: Botswana's track record in attracting FDI, the investment framework for FDI in Botswana, the impact of FDI on Botswana's national development objectives, and proposed recommendations and conclusions with regard to FDI policy in that country.